Detection of Determinants of Bank Sustainability Performance - Aprih Santoso; Siti Sofiatun (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2022)
Banks are financial institutions that function as a means of transactions carried out by the public in the form of deposits or loans. This study stems from the discovery of the problem of the company's sustainability level in commercial banks in the BUKU 4 group in 2019 which declined after being analyzed using the Financial Sustainability Ratio accompanied by conditions of economic growth in Indonesia which worsened from the previous year. This study was conducted to determine the effect of financial ratios in the form of Return on Assets, Capital Adequacy Ratio, Loan to Deposit Ratio, and Non-Performing Loans on Financial Sustainability Ratio using quantitative research methods through multiple linear regression analysis. The use of a sample of 5 banks out of 7 population banks was determined using the purposive sampling method and using quarterly company reports from 2017-2019. Based on the results of the study indicate that the Return on Assets, Loans to Deposit Ratio, and Non-Performing Loans have a significant effect on the Financial Sustainability Ratio. While the Capital Adequacy Ratio has no significant effect